The Rockefeller Foundation, the Museum of Modern Art Film Library, and Siegfried Kracauer, 1941. - Culbert, David (Historical Journal of Film, Radio & Television, 1993)
Features documents from the Rockefeller Archive in New York on the progression of Siegfried Kracauer's study of German wartime communication through film. Background on Kracauer; Rockefeller Foundation's grant to the Kracauer project; Release of films held in Ottawa to the Film Library of the Museum of Modern Art; English synopsis and summary appraisal of the `Hitlerjunge Quex'.